Optimizing throughput value through re-examining of 4G LTE infrastructure link budgets: A Case Study in Lubuk Kilangan - Yuhanef, Afrizal; Chandra, Dikky; Nabilla, Sisri; Ilham, Dirja Nur; Setiawan, Herry (Universitas Medan Area, 2024)
Broadband wireless access technology has taken the lead in communication technology development, enabling users to communicate with fast data speeds and extensive coverage.. Problems that frequently arise in mobile communication systems are the wide range of services and the level of network service quality. Thus, optimization is carried out to improve network quality in the Lubuk Kilangan area by using the drive test method to determine the quality of the network and bad spot areas and analyzed using terms discovery software. The reason behind the findings of this study is that the optimal link budget value for 4G LTE infrastructure in Lubuk Kilangan is higher than the current industry standard due to the unique characteristics of the area. According to the analysis and calculation of the link budget, power additions, and antenna tilting alterations were carried out for optimization. The power quality of the RSRP parameter increased from the fair (orange) area of 2.58 to 0.29. For the SINR parameter, For the SINR parameter, there was also an increase in quality at poor category locations in the KPI parameters (Range RSRP) locations from 0.08% to 0.05%, resulting in SINR bad spots decreasing. The proportion for Throughput after optimization remains the same, at 100%. Indicating that there had been a good increase in the coverage area, making the coverage in the Lubuk Kilangan area good. It is necessary to conduct a deeper study by comparing several types of antenna orientation, including tilt, depending on various factors such as the deployment scenario, coverage requirements, interference considerations, and the specific characteristics of picocells, femtocells, and repeaters. Future research could explore the impact of other factors, such as network topology and user behavior, on link budget optimization of 4G LTE infrastructure in different contexts